Assessment of efficiency and safety of application of the reproduced drug of Mertenil® according to MSCT-coronary angiography - Malov A.A.; Feiskhanova L.I. (Системные гипертензии, 2016)
In article possibility of an assessment of efficiency of therapy by the reproduced drug Mertenil of production of JSC Gideon Richter (Hungary) appointed for the purpose of primary prevention of the cardiovascular diseases. Increase of level of lipoproteid of the low density is one of the most powerful risk factors of death. Today therapy of a statin is carried out both for secondary and for primary prevention of cardiovascular diseases. For an assessment of dynamics of atherosclerotic processat patients with the diagnosis: CHD hypercholesterolemia without visual verification of defeat of the proximal coronary course possibility of use of a multispiral computer tomography of coronary arteries with calculation of a coronary calcic index is considered.